(untitled) (Communications in Computational Physics, 2018)
We compute multivalued solutions of one- and two-dimensional pressureless gas dynamics equations by deterministic particle methods. Point values of the computed solutions are to be recovered from their singular particle approximations using some smoothing procedure. We study several recovery strategies and demonstrate ability of the particle methods to achieve high resolution.